[The term mixed leg ulcer should no longer be used today]. - Dissemond, J.; Bültemann, A.; Gerber, V.; Motzkus, M.; Rembe, J. D.; Erfurt-Berge, C. (Die Dermatologie, 2023)
A wound on the lower legs of patients with chronic venous insufficiency (CVI) and peripheral arterial disease (PAD) is today usually referred to as a mixed leg ulcer. This does not take into account the different stages of the diseases and, thus, their pathophysiological relevance. In everyday clinical practice, this often leads, among other things, to these patients not receiving compression therapy. The multidisciplinary professional association Initiative Chronische Wunden (ICW) e. V., therefore, recommends that this undifferentiated and misleading term should no longer be used. Instead, a leg ulcer with advanced CVI and concomitant PAD in stage I-IIb according to Fontaine or Rutherford category 0-3 should be classified as a venous leg ulcer, while a leg ulcer with advanced PAD in stage III or IV according to Fontaine or Rutherford category 4-6 and advanced CVI is termed an arteriovenous leg ulcer. A leg ulcer in advanced PAD stage IV according to Fontaine or Rutherford category 5 or 6 without advanced CVI is called an arterial leg ulcer. Other relevant comorbidities with an influence on wound healing should also be described separately.
EVALuna2:539121